UPAYA KEPALA MADRASAH ALIYAH DALAM MENINGKATKAN KESADARAN SHALAT DZUHUR BERJAMAAH DI PONDOK PESANTREN - Devi Sartika; Lukman Asha; Abdul Sahib; Elce Purwandari; Rinsi Aura (STAI Ma'had Aly Al-Hikam Malang, 2022)
The madrasa head is a real example or role model for madrasa residents. Therefore the madrasa head must provide an example of the policies and programs that are made. This study aims to determine the efforts of the head of the madrasah aliyah in increasing awareness of the midday prayers in the congregation at the Bahrul Ulum Rantau Jaya Islamic boarding school. The method used in this research is the qualitative method. The number of research subjects was 18 people. Data collection techniques using observation, interviews, and documentation. Data analysis techniques in this study used data reduction, data presentation, and drawing conclusions. The results of the study found that the efforts of the head of the aliyah madrasah in increasing the awareness of students in the midday prayers in the congregation were by improving oneself, working with teachers, homeroom teachers, waka, student guardians, organizations in the madrasa, and students. Carry out good supervision, following up on the results of supervision carried out in management, regulations, punishments, and others.